Developing Effective User Acquisition Strategies for The Early Stages of The Socles App - Rachel Thalia; Fitri Aprilianty (Mandalika Journal of Business and Management Studies, 2025)
The The rapid growth of social media has transformed global interactions, often leading to superficial connections, particularly among younger generations. Socles, an early-stage social media startup in Indonesia, seeks to address this issue by fostering genuine relationships through its Socles App, which is designed specifically for Generation Z. The platform emphasizes authenticity and meaningful connections by encouraging offline interactions and offering interactive social games. However, Socles faces significant challenges in acquiring its initial user base, which is critical for its growth. To overcome these challenges, this study applies a strategic management approach to develop targeted user acquisition strategies, with a focus on capturing and retaining user interest in a competitive digital landscape. Utilizing the AIDA model—Attention, Interest, Desire, and Action—the research framework evaluates Socles' internal situation and analyzes the external environment through tools such as PESTEL and Porter’s Five Forces models. Additionally, competitor and trend analyses, along with market insights, are incorporated to inform strategic recommendations. A SWOT analysis synthesizes these findings to guide actionable strategies. The study employs qualitative data from interviews with internal teams and potential users, along with quantitative data from surveys of Indonesian university students, to gain a comprehensive understanding of market preferences. The research concludes with strategic recommendations aimed at enhancing Socles' overall business readiness. This approach offers valuable insights for other startups in the social media industry looking to learn from the Socles case.